1971
DOI: 10.1126/science.174.4013.1025
|View full text |Cite
|
Sign up to set email alerts
|

Subhuman Primate Diploid Cells: Possible Substrates for Production of Virus Vaccines

Abstract: Results of a program for development of new cell lines suggest that it it possible to establish cell lines from both rhesus and African green monkeys which are comparable to diploid lines of human origin, and that these monkey lines should be candidates for use in the production of virus vaccines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
7
0

Year Published

1972
1972
1986
1986

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 5 publications
2
7
0
Order By: Relevance
“…FRhL-2 was nonpermissive to HSV; only human diploid cells were permissive to CMV. This confirmed the results reported by Petricciani et al (10). It is also relevant to refer that Kubicek et al (7) observed no CPE of HSV in fetal rhesus monkey foreskin cell (rhfs 2), and Nii (9) reported abortive infection of HSV in an established cell line of rhesus monkey kidney cell (LLC-MK2).…”
supporting
confidence: 87%
See 1 more Smart Citation
“…FRhL-2 was nonpermissive to HSV; only human diploid cells were permissive to CMV. This confirmed the results reported by Petricciani et al (10). It is also relevant to refer that Kubicek et al (7) observed no CPE of HSV in fetal rhesus monkey foreskin cell (rhfs 2), and Nii (9) reported abortive infection of HSV in an established cell line of rhesus monkey kidney cell (LLC-MK2).…”
supporting
confidence: 87%
“…In fact, this was true in virological diagnosis of patients with eczema herpeticum, generalized herpes zoster and eczema vaccinatum (unpublished data). Vaccinia virus replicated in ERhL, as reported by Petricciani et al (10), producing intracytoplasmic inclusion bodies.…”
supporting
confidence: 54%
“…Metaphases from a cell culture of Macaco mulatto in the 71st passage; note the difference in size between the chromosome with the achromatic region proximal to the centromere (single arrows) and those chromosomes in which the achromatic region is distal (double arrows), x 2,400. tions. Although diploid cell lines from some subhuman primate tissue have been propagated for as many as 36 passages [Petricciani et al, 1971;Coop er, 1972], our cultures were aneuploid and contained metaphases with al tered chromosomes by the 17th subculture. Focusing our attention on the evolution of the marked chromosomes in our cell line, we found them to be characterized by an easily recognizable achromatic region amply documented in several primate species.…”
Section: Discussionmentioning
confidence: 99%
“…These strains were subsequently plaque purified and passaged in primary or secondary AGMK cells. The final passages of both animal strains were in DBS-FRhL-2 cells, a simian embryonic diploid cell strain (21). The RRV seed used for gene reassortment represented a later passage of lot RRV-1 (prepared at Flow Laboratories, Inc.) in DBS-FRhL-2 cells.…”
Section: Methodsmentioning
confidence: 99%